2004
DOI: 10.1101/gr.3021305
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the chicken and turkey genomes reveals a higher rate of nucleotide divergence on microchromosomes than macrochromosomes

Abstract: A distinctive feature of the avian genome is the large heterogeneity in the size of chromosomes, which are usually classified into a small number of macrochromosomes and numerous microchromosomes. These chromosome classes show characteristic differences in a number of interrelated features that could potentially affect the rate of sequence evolution, such as GC content, gene density, and recombination rate. We studied the effects of these factors by analyzing patterns of nucleotide substitution in two sets of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
117
8
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 146 publications
(149 citation statements)
references
References 58 publications
23
117
8
1
Order By: Relevance
“…Importantly, the d N /d S ratio was still significantly higher (P = 0.04) in the Z-linked genes (0.110) than in genes that mapped to chicken chromosomes 1-10 (0.0948). The reduction in d S for chromosomes 1-10 compared to all autosomes is consistent with previous observations of a lower mutation rate on macro-than on microchromosomes (International Chicken Genome Sequencing Consortium 2004; Axelsson et al 2005). This seems largely because of the higher GC content of microchromosomes and the positive correlation between GC and substitution rate in birds (Webster et al 2006).…”
Section: Divergence Datasupporting
confidence: 80%
“…Importantly, the d N /d S ratio was still significantly higher (P = 0.04) in the Z-linked genes (0.110) than in genes that mapped to chicken chromosomes 1-10 (0.0948). The reduction in d S for chromosomes 1-10 compared to all autosomes is consistent with previous observations of a lower mutation rate on macro-than on microchromosomes (International Chicken Genome Sequencing Consortium 2004; Axelsson et al 2005). This seems largely because of the higher GC content of microchromosomes and the positive correlation between GC and substitution rate in birds (Webster et al 2006).…”
Section: Divergence Datasupporting
confidence: 80%
“…Specifically, we found that K S distribution differences between genes on chicken micro-and macrochromosomes also remain significant when only considering genes exhibiting similar G+C contents, or G+C percentage at fourfold degenerate sites 126 (Table 9). Higher neutral divergence rates are also seen on microchromosomes when genes are compared between chicken and turkey genomes 127 . Second, subtelomeric sequences, which are often duplicated and polymorphic 86,128 , also show elevated neutral substitution rates.…”
Section: Synonymous Substitution Ratesmentioning
confidence: 93%
“…Both chicken and turkey belong to the order Galliformes and show a neutral autosomal sequence divergence of $10% (Axelsson et al 2005). We found 11,011 interspecific indels in the alignments after filtering for repetitive arrays using the same criteria as in the polymorphism data set.…”
Section: à13mentioning
confidence: 89%